Mulheres em situação de violência e atenção em saúde mental: um estudo no município de Natal (RN) - Barbosa, Lais Barreto (2013)
The present study aims to meet the attention given to women with mental health needs in specialized services for the fight against violence against women, as well as psychosocial care network in the municipality of NatalRN. It is a qualitative research characterized as research-intervention that took place in the year 2011. The study started in the Centre of Reference in which individual semi-structured interviews were carried out directed to the coaching staff and manager, in order to know the care offered in relation to the aforementioned clientele. From the Reference Centre were identified through analysis of registration records, the routes traversed by users through the network of psychosocial care and hospital network. After the identification of the same were visited two day-care Centers, two psychiatric hospitals, a basic health Unit and the local shelter. In these organizations was investigated the reception and procedures offered to users in situations of violence, the knowledge of policies for women and the coordination with the attention to women, through interviews with semi-structured individual scripts directed to professionals. The interviews were analyzed taking as starting point the theoretical framework of French Institutional Analysis, which includes the assumption of events analysers for the critical reading of dimensions introduced in the practices of care of the teams that took part in the study. The survey results revealed difficulties on the part of the same host of users with this profile, both in the face of violence as services in mental health services. This fact led to the lack of support under the guarantee of their rights, ceasing the possibilities of confronting the situations of violence, as well as in the context of mental health care